Causality Model of Trading Variables Between Trading Volume, Bid-Ask Spreads, and Stock Return Volatility (Case Study: Bisnis-27 Index) - Agung, Andi; Zaqiyah, Arfatuz; Rozikin, Muhammad; Wafa, Moh. Shohibul; Nuha, Agusyarif Rezka; Sulistyono, Eko (JURNAL SINTAK, 2024)
This research explores the causality model between trading volume, bid-ask spread, and stock return volatility in the business index-27. Utilizing historical data, Granger causality analysis is employed to determine the direction and strength of the relationships between these variables. The findings reveal significant causal relationships among trading volume, bid-ask spread, and stock return volatility. These findings offer valuable insights into understanding stock market dynamics and their implications for investment decision-making. Moreover,This article contains an analysis of the relationship between stock trading variables within the scope of two main hypothesis namely the mixture of distribution hypothesis (MDH) and the sequential information arrival hypothesis (SIAH). The calculation results identify that for most stocks there is a one way Granger causality relationship between trading volume and return volatility, which is not sufficient evidence to support the MDH theory.